Aplikasi Kacang Koro Pedang ( Canavalia ensiformis L.) Terfermentasi Rhizopus oligosporus terhadap Kinerja Produksi dan Kualitas Telur Burung Puyuh - Sri Utami; Sariffudin Fatmona; Sri Wahyuni (Jurnal Penelitian Pendidikan IPA, 2024)
Scarcity and high cost of raw materials for poultry feed are the main problems that can hamper poultry production. An alternative ingredient that can be used in feed is koro beans. The aim was to determine the effect of rations containing fermented jack beans, Rhizopus oligosporus, on the production performance and quality of quail eggs. The analysis used a completely randomized design consisting of 5 treatments; Each treatment was repeated 4 times and each replication consisted of 15 quail. Four types of rations contained fermented sword bean at 7.5, 15, 22.50 and 30% and the control ration did not contain fermented sword bean. The parameters observed included feed consumption, egg production, feed conversion, shell thickness, egg yolk color and egg yolk cholesterol. The level of fermented sword bean in the ration of laying quail did not have a significant effect (p>0.05) on feed consumption and eggshell thickness. However, egg weight, daily egg production, feed conversion, yolk color intensity and yolk cholesterol were significantly influenced by fermented treatment (p<0.05). Sword beans fermented by R. oligosporus can be used as a food ingredient in egg-laying quail feed formulations to increase the quantity and quality of quail eggs.